p38α Mitogen-Activated Protein Kinase—An Emerging Drug Target for the Treatment of Alzheimer’s Disease - Jan Detka; Natalia Płachtij; Martyna Strzelec; Aleksandra Manik; Kinga Sałat (Molecules)
Alzheimer’s disease (AD) is a neurodegenerative disorder, characterized by the formation of amyloid β and tau protein aggregates in the brain, neuroinflammation, impaired cholinergic neurotransmission, and oxidative stress, resulting in the gradual loss of neurons and neuronal function, which leads to cognitive and memory deficits in AD patients. Chronic neuroinflammation plays a particularly important role in the progression of AD since the excessive release of proinflammatory cytokines from glial cells (microglia and astrocytes) induces neuronal damage, which subsequently causes microglial activation, thus facilitating further neurodegenerative changes. Mitogen-activated protein kinase (MAPK) p38α is one of the key enzymes involved in the control of innate immune response. The increased activation of the p38α MAPK pathway, observed in AD, has been for a long time associated not only with the maintenance of excessive inflammatory process but is also linked with pathophysiological hallmarks of this disease, and therefore is currently considered an attractive drug target for novel AD therapeutics. This review aims to summarize the current state of knowledge about the involvement of p38α MAPK in different aspects of AD pathophysiology and also provides insight into the possible therapeutic effects of novel p38α MAPK inhibitors, which are currently studied as potential drug candidates for AD treatment.